2008
DOI: 10.1073/pnas.0800793105
|View full text |Cite
|
Sign up to set email alerts
|

ATP release through connexin hemichannels and gap junction transfer of second messengers propagate Ca 2+ signals across the inner ear

Abstract: Our results demonstrate that these connexins play a dual crucial role in inner ear Ca 2؉ signaling: as hemichannels, they promote ATP release, sustaining long-range ICS propagation; as GJ channels, they allow diffusion of Ca 2؉ -mobilizing second messengers across coupled cells.deafness ͉ mouse models ͉ P2x7 receptor ͉ pannexin ͉ biosensor cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
391
2
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 306 publications
(416 citation statements)
references
References 62 publications
(94 reference statements)
16
391
2
1
Order By: Relevance
“…This phenomenon could be blocked by extracellular apyrase-which hydrolyses ATP, and the PLC inhibitor U73122. The findings, including block of the Ca 2+ wave propagation using carbenoxolone, a gap junction blocker, suggested that the connexin hemichannel conduit for the ATP release in the cochlea [7,37] is coupled to P2Y receptor signaling [3]. Our data showing prominent P2Y2 receptor expression at this site is consistent with the initial immunolocalization of P2Y 2 to the Hensen's cell region by Gale et al [3].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This phenomenon could be blocked by extracellular apyrase-which hydrolyses ATP, and the PLC inhibitor U73122. The findings, including block of the Ca 2+ wave propagation using carbenoxolone, a gap junction blocker, suggested that the connexin hemichannel conduit for the ATP release in the cochlea [7,37] is coupled to P2Y receptor signaling [3]. Our data showing prominent P2Y2 receptor expression at this site is consistent with the initial immunolocalization of P2Y 2 to the Hensen's cell region by Gale et al [3].…”
Section: Discussionsupporting
confidence: 91%
“…ATP release has also been observed in the supporting cells in and adjacent to the organ of Corti [3][4][5] where the mechanism involves P2Y and P2X receptor signaling that could be induced by hair cell damage. Connexin and pannexin hemichannels are implicated in the ATP release mechanism [6][7][8]. The stria vascularis in the lateral wall of the cochlea is the source of the K + flux into scala media that establishes the driving force for sound transduction (the positive endocochlear potential).…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that cochlear ATP is mainly released from cochlear supporting cells via gap junction hemichannels [24]. In the local area near the cell surface, the ATP concentration would be high and can reach micromolar levels [24,28]. In this study, we found that the application of submicromolar and nanomolar ATP could evoke inward currents in the cochlear supporting cells (Fig.…”
Section: Discussionsupporting
confidence: 50%
“…This close timing between the loss of tdTomato and the constriction by the SC suggests that SCs were likely responding to HC death, possibly signaled by the release of intracellular ATP. 4,40,41 It is also possible that HCs prime their surrounding SCs with a stress signal before they lose membrane integrity. The idea that HCs may signal their impending death is supported by our observation that dying HCs shrink for several hours before losing membrane integrity, a phenomenon that occurred in both neomycin-and cisplatintreated utricles.…”
Section: Discussionmentioning
confidence: 99%